An ovulatory menstrual health literacy program within a Health Promoting School framework: reflections from school staff - Roux, Felicity; Hendriks, Jacqueline; Burns, Sharyn; Chih, HuiJun (Frontiers in Education, 2023)
Poor ovulatory menstrual (OM) health experiences and low levels of OM health literacy compromise the future adult health and wellbeing of female adolescents. This qualitative study sought reflections from secondary school staff on an intervention adopting the Health Promoting School (HPS) approach which aimed to enhance wellbeing through improving OM health literacy. Twenty female school staff from ten schools participated: three deans, 11 Health and Science teachers and six healthcare professionals. Five interviews and three focus groups were conducted, and 12 anonymously notated booklets of the program were returned. Reflective thematic analysis identified six themes: a need for OM health literacy; curricular challenges; teaching perspectives; school socio-emotional environment; community engagement; and resourcing needs. Alignment with a HPS-framework may resolve some barriers to future program implementation, such as curricular restrictions, interprofessional co-ordination and community engagement. Additional barriers, relating to menstrual disdain, knowledge gaps and an absence of professional development, may be addressed with training to ensure that OM health education is framed positively and addresses student wellbeing.